2021
DOI: 10.1177/07488068211065833
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal Preservation Rhinoplasty: A Literature Review

Abstract: Acceptance of the preservation principle in rhinoplasty surgery has increased dramatically, and surgeons worldwide are now performing preservation rhinoplasty, leading to an expanding list of indications and techniques. Rhinoplasty surgeons are increasingly opting for rhinoplasty preservation because of its conservative approach and more predictable outcome. This review aims to evaluate the efficacy of dorsal preservation rhinoplasty, as well as the techniques, indications, surgical protocols, complications, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Compared with classical structural rhinoplasty techniques, preservation rhinoplasty is a very popular technique and has many advantages, such as achieving a more natural middle vault. 9 , 10 Because there is no need for middle vault repair, the results are closer to the natural look in terms of the middle vault. In our technique, the middle vault is preserved, the bony cap is mobilized and preserved, and the lateral nasal bones are equalized by a piezo device or classical osteotomes.…”
Section: Introductionmentioning
confidence: 88%
“…Compared with classical structural rhinoplasty techniques, preservation rhinoplasty is a very popular technique and has many advantages, such as achieving a more natural middle vault. 9 , 10 Because there is no need for middle vault repair, the results are closer to the natural look in terms of the middle vault. In our technique, the middle vault is preserved, the bony cap is mobilized and preserved, and the lateral nasal bones are equalized by a piezo device or classical osteotomes.…”
Section: Introductionmentioning
confidence: 88%
“…While, this study demonstrated no conclusive relationship between facial esthetics and the golden ratio across all ethnicities, the alignment, symmetry, and proportion of the face, which are fundamental elements of facial beauty, are still frequently assessed using the golden ratio in facial analysis (19). Moreover, according to a Stevens et al study in 2021, the golden ratio is a useful tool for facial analysis and dorsal preservation rhinoplasty, which is a surgical procedure that tries to maintain the nose's natural form while enhancing its esthetic (20).…”
Section: Golden Proportion In Facial Analysismentioning
confidence: 99%
“…The rate post-rhinoplasty is very low because of the assortment of this technique and the trouble in illustrating patient expectations. The selection of patients is extremely important in rhinoplasty, as excellent surgical outcomes may not happily inspire many patients [23,24].…”
Section: Esthetics Through Rhinoplastymentioning
confidence: 99%